1989
DOI: 10.3109/00365528909092245
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal Motility and Lower Oesophageal Sphincter Competence in Progressive Systemic Sclerosis and Localized Scleroderma

Abstract: Oesophageal motility and lower oesophageal sphincter (LOS) competence were investigated in 13 patients with progressive systemic sclerosis (PSS) and in 16 patients with localized scleroderma (LS) by means of oesophageal manometry and 24-h pH monitoring of the distal oesophagus. Results were compared with those of a control group consisting of asymptomatic volunteers. Marked abnormalities in oesophageal motility and in acid exposure in the distal oesophagus were observed in PSS patients only. The mean resting p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…76 In contrast to these studies, esophageal dysmotility was shown not to correlate with these antibodies in another study. 52 Compared with limited disease, diffuse PSS is associated with greater abnormalities on scintigraphy, 64,72 manometry, 51,59,71 pH studies, 59 and endoscopy. 51 However, other investigators reported no differences in the esophageal abnormalities in diffuse versus limited PSS.…”
Section: Esophageal Dysfunction In Disease Subsetsmentioning
confidence: 99%
See 1 more Smart Citation
“…76 In contrast to these studies, esophageal dysmotility was shown not to correlate with these antibodies in another study. 52 Compared with limited disease, diffuse PSS is associated with greater abnormalities on scintigraphy, 64,72 manometry, 51,59,71 pH studies, 59 and endoscopy. 51 However, other investigators reported no differences in the esophageal abnormalities in diffuse versus limited PSS.…”
Section: Esophageal Dysfunction In Disease Subsetsmentioning
confidence: 99%
“…It is abnormal in 54% to 86% of patients with PSS. 45,46,51,[57][58][59] Compared with non-PSS patients with similar degrees of esophagitis, the PSS patients had fewer reflux events but they were of significantly longer duration. 60 Aperistalsis correlated with increased numbers of distal reflux episodes with long duration, 22,45,46,61 although one study found that aperistalsis correlated with proximal rather than distal reflux.…”
Section: Diagnosis Of Esophageal Dysfunctionmentioning
confidence: 99%
“…Esophageal involvement is the best known and most frequent gastrointestinal manifestation of systemic sclerosis (SSc) and occurs in 50-80% of patients [1][2][3]. Pathophysiologically, the primary event appears to be an abnormality in cholinergic neural function, which is followed by smooth muscle atrophy and fibrosis [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of SSc-induced gastrointestinal involvement seems to decline from the cranial to the caudal end of the gastrointestinal tract, with the oesophagus being affected in 60-80% [3][4][5] of cases, stomach and small intestine in 40-60% [3,6], the colon in 10-50% ] 7,8], and the anorectum probably only in sporadic cases [9]. In two cases reports, slceroderma has been reported to be associated with a thickened and fibrosed gallbladder wall [10] or gallbladder vasculitis [1 1].…”
Section: Introductionmentioning
confidence: 99%